Socio-Economic Determinants of Goat Milk Consumption by Rural Households in the Niger Valley of Benin and Implications for the Development of a Smallholder Dairy Goat Program - Icoutchika, Karl-Loïc Mawussé; Ahozonlin, Maurice Cossi; Mitchikpe, Comlan Evariste Simon; Bouraima, Oul'fath; Aboh, André Boya; Dossa, Luc Hippolyte (Frontiers in Sustainable Food Systems, 2022)
Goats, more popular than cattle in rural Benin, are mainly kept for meat production. Their milk is still not popular but can provide the much-needed nutrients for children in food-insecure households. The study aimed to explore the socio-economic factors affecting the attitude of rural households in the Niger Valley of Benin towards goat milk consumption. Data were collected through individual face-to-face interviews from 721 heads of households or their representatives. Binary logistic regression analysis was carried out to test the association between socioeconomic variables and goat milk consumption. Goat milk and its products were consumed in 14.7% of the surveyed households and were not traditionally part of the diets in the remaining 81.8 %. Their sensory qualities were further reasons reported by 18.4 % of respondents for their non-consumption. A household’s likelihood to consume goat milk or its derivatives was significantly influenced by the socio-cultural background of its head and whether it kept goats or not. The odds of goat milk and milk products consumption were 2.285 and 2.017 times higher respectively for households from Dendi and Peulh sociocultural groups. Despite the recorded cultural barriers, there is room for increasing goat milk consumption by rural households by increasing its availability and raising awareness of its nutritional and health benefits.